0898 Elevated Total Lung Capacity Attenuates Sleep-related Breathing Disorders In Chronic Obstructive Pulmonary Disease. (27th April 2018) - Herkenrath, S; Pepin, J; Treml, M; Arzt, M; Zeman, F; Penzel, T; Schöbel, C; Fietze, I; Sert Kuniyoshi, F; Lotz, G; Weissmueller, V; Hamerle, M; et al.
Abstract: Introduction: Lung function determines lung and upper airway volumes in COPD patients. Despite significant negative physiologic effects, hyperinflation, in COPD patients with overlap syndrome, may stretch the upper airway, decreasing pharyngeal collapsibility, thereby reducing the severity of sleep-related breathing disorders (SRBD). Therefore, we tested the hypothesis, that hyperinflation (increasing total lung capacity, TLC) is associated with lower severity of SRBD (apnea-hypopnea index, AHI). Methods: In this multi-center retrospective analysis, data from 81 COPD patients (65 ± 9 years, BMI 30 ± 8 kg/m 2, 27 women) who completed both diagnostic polysomnography and lung function testing were analyzed. Simple linear regression models were calculated to assess the impact of lung function parameters (VC, FEV1, FEV1/VC, TLC) on AHI. Furthermore, significant predictors (p<0.1) were added to a multiple linear regression model controlling for BMI, gender and age. Results: Fifty-four percent of the studied COPD patients had SRBD (AHI > 15/h). Among the variables tested in the simple linear regression analyses, only total lung capacity (TLC) showed a significant association with AHI (p=.019). All other lung function parameters were not significant (VC p=.315, FEV1 p=.330, FEV1/VC p=.566) and were thus excluded from the multiple linear regression model. In the multiple linear regression model, increasing TLC remained a significant predictor for lower AHI (B=-.22 (95%-CI: -.46, -.001), p=0.049, R 2 model =.10). Conclusion: Hyperinflation was significantly associated with lower severity of SRBD, independent of known key risk factors of SRBD. Data suggest that hyperinflation may attenuate SRBD. Support (If Any): Supported by Philips Respironics.